Global Player EU?: Eine ideologiekritische Metaphernanalyse - Bischof, Karin (transcript, 2015)
The EU and its metaphors – metaphors constitute a key reserve of political rhetoric. This book analyzes the metaphorization of the EU as a »Global Player« and its ideological content, which portrays Europe as a neoliberal and masculine project.